Pembelajaran daring materi bangun ruang pada Siswa Kelas V SD menggunakan pendekatan realistic mathematics education (RME) - Ismi Azhari Pangestu; Siti Ruqoyyah (IKIP Siliwangi, 2023)
The ability to understand about solid (geometry) for elementary school students in grade V is very important because it is one of the subjects in mathematics. However, the facts in the field have not been well honed. Many students have difficulty during the learning process, especially when the questions are presented in the form of stories related to everyday life. Through the Realistic Mathematics Education (RME), approach, students are able to understand about that problems using concrete objects, because students are directed to solve a problem through real-world situations. This study aims to examine the scenarios and implementations, students' and teacher's responses, difficulties experienced by students and teacher during online learning, and teacher's obstruction in implementing online learning. The research subject was done in grade V at elementary school in Bandung Barat. This research uses descriptive qualitative research. The instruments in this study consisted of observation sheets, questionnaires or attitude scales, interviews and written tests. The achievement of this study shows the expected results based on the post-test results on each item because it has increased. That way, the ability to understand about solid (geometry) using the Realistic Mathematics Education (RME), approach is better than before getting treatment using the Realistic Mathematics Education (RME), approach.